Explicație pas cu pas:
[tex]2x + 5 = - 11 \\ 2x = - 16 = > x = - 8[/tex]
[tex]3x + 87 = 0 \\ 3x = - 87 = > x = - 29[/tex]
[tex]x + 17 = 3 - x \\ 2x = - 14 = > x = - 7[/tex]
[tex]x - 3(2 - 4x) = 1 + 6x \\ x - 6 + 12x = 1 + 6x \\ 7x = 7 = > x = 1[/tex]
[tex](x + 1)(2x + 4) = 0 \\ x + 1 = 0 = > x = - 1 \\ si \\ 2x + 4 = 0 = > x = - 2[/tex]
[tex] |2x - 3| = 7 \\ 2x - 3 = - 7 \\ 2x = - 4 = > x = - 2 \\si \\ 2x - 3 = 7 \\ 2x = 10 = > x = 5[/tex]
[tex] |x + 3| = - 2 \\ dar \: |x + 3| \geqslant 0 \\ = > fara \: solutie[/tex]
=> x ∈ ∅